A daily cycle of White Collar Complex dephosphorylation sustains circadian rhythmicity in Neurospora - Bin Wang; Xiaoying Zhou; Jennifer J. Loros; Jay C. Dunlap (Proceedings of the National Academy of Sciences, 2026)
The transcription factor complex White Collar Complex (WCC) functions both as a photoreceptor and as the circadian positive element. In response to light, WCC acutely activates ~5% of all genes, whereas in the dark it influences expression of about 40% of the transcriptome. Among WCC targets is frq , which is acutely light-activated through the pLRE ( proximal Light-Response Element ) and circadian-regulated through the C-box ( Clock-box ) promoter element that is not responsible for light-driven expression. The FRQ–FRH complex (FFC), which includes CK-1a, represses WCC activity at the C-box by phosphorylating WCC at >95 sites, but FFC has no described role in the light. We validated the expectation that FFC also silences C-box promoters in constant light, thereby confirming two classes of WCC targets: C-box -like genes that are normally repressed in light and pLRE -like genes that remain light-active despite FFC-driven WCC phosphorylation. Derepression of C-box -like promoters in frq -null fungi may explain reported noncircadian phenotypes such as reduced virulence and conidiation. Reanalysis of WCC circadian regulation revealed that, while most WCC is phosphorylated and repressed at dusk, subsequent circadian activation results from transient dephosphorylation of only a small subset of the WCC pool. This small active pool drives frq expression, nucleating the FFC, which rephosphorylates WCC to repress it again, generating a phosphorylation/dephosphorylation cycle that can persist for days without new WCC synthesis. The realization that both FFC and WCC are regulated primarily through phosphorylation rather than protein turnover leaves the circadian oscillator looking much like a “phoscillator,” emphasizing the primacy of posttranslational regulation in timekeeping.